TRANSNATIONAL ORGANISED CRIME IN INDONESIA: THE NEED FOR INTERNATIONAL COOPERATION - Mitchell, James N (Faculty of Law, Universitas Brawijaya, 2016)
This article examines the growing infuence of transnational organised crime on the nations of South East Asia. Human trafficking, maritime piracy, terrorism and wildlife trafficking are major transnational crimes that cause significant harm to both individuals and national economies. This article examines the continuing domestic and international legislative, law enforcement and policy efforts of South East Asian nations to address transnational organised crime. it is concluded that to effectively counter transnational organised crime there is a need to employ international cooperation that is focused on addressing the unique factors of each crime.